THE IMPACT OF STRATEGIC FACTORS OF WASTE MANAGEMENT ON ENVIRONMENTAL PROTECTION IN KAZEROON CITY IN 2017 - Mehbodi, Mohammadrafi; Yazdanpanah, Abbas; Alvaani, Jamalledin (Universal Journal of Pharmaceutical Research, 2018)
Objective: Today, environment protection is one of main pillars of observing human right, so that protection and maintenance of environment is one of main duties of present and future. After investigating and identifying environmental factors including internal and external environment of waste management and preparing a list of the most important strengths and weaknesses, opportunities and threats ( 40 factors) and selecting the most important factors participatory (24 factors) using EFE and IFE matrix. Methods: Factors were analyzed and evaluated and the score was determined and in the following, using the matrix and regarding internal and external factors, the most suitable strategies were introduced for optimal management of waste system of the studied region and in the next stage, using the matrix score of evaluating internal and external factors and strategies of matrix formation matrix, the present status of the organization (IE), the preservative approach was selected as goal approach and attraction of any preservative strategies was specified in the qualitative strategic planning matrix (QSPM). Results: On the basis of results should be said that the order of approaches priority is based on their so-called genera weight rate and movement towards sustainable development that based on the attraction score, the priorities became in this order that the first priority is related to strategy and then respectively optimizing various stages of wastes management. Conclusion: In conclusion, by increasing awareness and changing the individuals attitude towards correct method of waste management like reduction of waste production, separation of recyclable materials at home and method of collecting through holding training classes, preparing and distributing advertising posters in the cities, implementing plan of separation from origin and its success requires public participation and cooperation. Peer Review History: Received 19 May 2018; Revised 8 July; Accepted 11 September; Available online 15 September 2018 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewer(s) detail: Dr. Mohamed Salama , Modern University for Technology & Information, Egypt, salama47@yahoo.com Dr. George Zhu , Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com